2008
DOI: 10.1016/j.cellbi.2008.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of small interfering RNAs targeting MAPK1 on gene expression profile in HeLa cells as revealed by microarray analysis

Abstract: The mitogen activated protein kinases (MAPK) signaling cascade plays an important role in cell life. We proved that small interfering RNAs targeting MAPK1 (siRNA-2) could inhibit HeLa cell growth, but the effects of siRNA-2 on gene expression profile were unclear. Using Affymetrix GeneChip HG-U133A 2.0, we identified the long-term changes for 48 h in gene expression profile in HeLa cell treated by siRNA-2. The results showed that expressions of 181 genes were altered by siRNA-2 and were divided into two groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
2
7
0
Order By: Relevance
“…Importantly, most of these signals are derived from non-chr21 DEGs, and would be missed by analyses focused specifically on chr21-encoded genes (Figure 2A). This analysis also identified two known repressors of IFN signaling, MAPK1 and TRIM24, as upstream regulators inactivated in T21 cells, consistent with activation of the IFN pathway (Huang et al, 2008; Tisserand et al, 2011). As an example of how the RNA-seq data supports the upstream regulator prediction by IPA, Figure 2B shows the gene network centered on the ligand IFNA2 as a potential driver of consistent gene expression changes.…”
Section: Resultssupporting
confidence: 58%
“…Importantly, most of these signals are derived from non-chr21 DEGs, and would be missed by analyses focused specifically on chr21-encoded genes (Figure 2A). This analysis also identified two known repressors of IFN signaling, MAPK1 and TRIM24, as upstream regulators inactivated in T21 cells, consistent with activation of the IFN pathway (Huang et al, 2008; Tisserand et al, 2011). As an example of how the RNA-seq data supports the upstream regulator prediction by IPA, Figure 2B shows the gene network centered on the ligand IFNA2 as a potential driver of consistent gene expression changes.…”
Section: Resultssupporting
confidence: 58%
“…Previously, Kalvakolanu and colleagues showed that upon IFNγ induction C/EBP-β is phosphorylated by MAPK1/2 to activate expression of the GATE-driven genes (Roy et al, 2002). However, this model does not explain up-regulation of the GATE-driven genes when only MAPK1 is knocked down in cells (Huang et al, 2008) or the suppression of IRF9 and OAS1 8 hours post IFNγ-treatment (Figure 5J). Based on the newly discovered DNA-binding activity of MAPK1, a plausible explanation is that expression of the GATE-driven genes is dictated by competitive binding of C/EBP-β and MAPK1 to GATE element.…”
Section: Discussionmentioning
confidence: 92%
“…To identify targets of MAPK1 and thereby gain clues to its function, we compared the gene-expression profiles of HeLa cells to those of the cells in which MAPK1 is knocked down using siRNA (Huang et al, 2008). Because MAPK1 showed a dose-dependent repression of luciferase activity in the assays described above, we collected the promoter sequences of 82 genes that showed at least a two-fold up-regulation of expression following siRNA-mediated knockdown of MAPK1 when compared to the control.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that siRNA targeting for the MAPK p42 gene partially inhibits proliferation and increases apoptosis in human cervical carcinoma HeLa cells (18,19). Results of a microarray analysis showed that MAPK p42 siRNA inhibited cell growth through the regulation of cell cycle control and apoptosis and induced an interferon-like response in HeLa cells (20). In order to confirm the specific effects of siRNA on MAPK p42 and the non-specific interferon-like response effect, the roles of siRNA and U0126, an inhibitor of MAPK p42, were compared in HeLa cells.…”
Section: Introductionmentioning
confidence: 99%